Peran Psikologi Agama dalam Pembentukan Kesehatan Mental Individu - Mohammad Farhat; Nazril Mirza Syaifullah; Muhammad Ridho Alfarizy; Yuminah Rahmatullah (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
Mental health is a crucial aspect of life. Humans live not only by maintaining their physical health but also by taking care of their mental well-being. Mental health can be influenced by various factors, one of which is religion. In this regard, religion plays a significant role in maintaining a person's mental health. This study was conducted to examine the role of religion in human mental health. The research used a qualitative approach with a literature study method. A literature study is a method that relies on secondary data sources from various existing scientific references, conducted by reading books, journals, or articles with relevant topics to be analyzed and explored further. This study found several important roles of religious psychology in shaping mental health, along with its various functions.